2018
DOI: 10.1002/jcp.26752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol on fibroblasts from postmenopausal idiopathic carpal tunnel syndrome patients

Abstract: Fibrosis of the subsynovial connective tissue (SSCT) is a characteristic finding in patients with idiopathic carpal tunnel syndrome (CTS). Idiopathic CTS frequently occurs in postmenopausal women; therefore, female steroid hormones, especially estrogens, may be involved in its development. In this study, we evaluated the effect of the estradiol on the expression of genes and proteins related to fibrosis of SSCT fibroblasts from patients with idiopathic CTS. This study included 10 postmenopausal women (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…2-7 It has been suggested by other authors that the higher incidence in older women, who are most likely postmenopausal, is likely related to a decrease in estrogen levels during menopause and that estrogen could play a protective role in developing CTS. 8,9 We also found a low incidence of CTS among the Asian population. However, we believe that this is reflective of the demographics at our institution and would benefit from further investigation in a multi-institutional study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…2-7 It has been suggested by other authors that the higher incidence in older women, who are most likely postmenopausal, is likely related to a decrease in estrogen levels during menopause and that estrogen could play a protective role in developing CTS. 8,9 We also found a low incidence of CTS among the Asian population. However, we believe that this is reflective of the demographics at our institution and would benefit from further investigation in a multi-institutional study.…”
Section: Discussionsupporting
confidence: 62%
“…[3][4][5] Postmenopausal women, in particular, have a higher risk of developing CTS. 8,9 Ulnar nerve compression at the elbow, the second most common peripheral neuropathy, has an annual incidence of 30 cases per 100 000 person-years. 10 It generally occurs in men, 2,4,[10][11][12][13] those with diabetes, 4,14,15 smokers, 4,12,16 and those whose work activities require maintaining their elbows in flexed positions for prolonged periods of time, such as keyboard typing, talking on the telephone, or repetitive lifting of heavy objects.…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulated network constructed in this study revealed the potential interaction and/or regulation of ESR1 with many proteins associated with cell adhesion, ECM, and cholesterol metabolism. For example, Esr1 has also been shown to mediate the Col1a1 reduction signaling ( 66 ). Furthermore, estradiol regulates MMP2 and its inhibitor TIMP1 through ESR1, affecting ECM degradation ( 67 ).…”
Section: Discussionmentioning
confidence: 99%